2015
DOI: 10.12659/msm.894238
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Hospitals: It Was, Is Now, and Must Not Remain a Problem!

Abstract: BackgroundMalnutrition is an under-recognized problem in hospitalized patients. Despite systematic screening, the prevalence of malnutrition in the hospital did not decrease in the last few decades. The aim of our study was to evaluate the prevalence of malnutrition and to determine the explicit daily calorie intake of hospitalized patients, to identify the risk factors of developing malnutrition during hospitalization and the effect on the financial reimbursement according to the German DRG-system.Material/Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 24 publications
5
64
0
6
Order By: Relevance
“…Domestic and foreign literature shows that 25%–60% of hospitalized patients suffer from malnutrition (14,15). In clinical practice, nutritional support and nutrition therapy are always delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Domestic and foreign literature shows that 25%–60% of hospitalized patients suffer from malnutrition (14,15). In clinical practice, nutritional support and nutrition therapy are always delayed.…”
Section: Discussionmentioning
confidence: 99%
“…13 The risk of malnutrition in hospitalized patients would increase when the patient is on bed rest. 12 All patients with severe malnutrition in this study have experienced change of food intake. Most patients with mild-moderate malnutrition and severe malnutrition had suboptimal solid diet (60% and 73.9%), suggesting that the majority of the patients are still able to eat but the intake is less than their nutritional needs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, he reported that the prevalence of malnutrition was increased in patients with hepatic, gastrointestinal disease, depression or dementia, always evidencing that the most important risk factors for malnutrition were bed rest and immobility [17].…”
Section: Nutritional Status Assessmentmentioning
confidence: 99%